Precision Medicine in Children and Young Adults with Hematologic Malignancies and Blood Disorders: The Columbia University Experience - Marks, Lianna J.; Oberg, Jennifer A.; Pendrick, Danielle; Sireci, Anthony N.; Glasser, Chana; Coval, Carrie; Zylber, Rebecca J.; Chung, Wendy K.; Pang, Jiuhong; Turk, Andrew T.; Hsiao, Susan J.; Mansukhani, Mahesh M.; et al. (Frontiers in Pediatrics, 2017)
Background The advent of comprehensive genomic profiling has markedly advanced the understanding of the biology of pediatric hematological malignancies, however, its application to clinical care is still unclear. We present our experience integrating genomic data into the clinical management of children with high-risk hematologic malignancies and blood disorders and describe the broad impact that genomic profiling has in multiple aspects of patient care. Methods The Precision in Pediatric Sequencing Program at Columbia University Medical Center instituted prospective clinical next-generation sequencing (NGS) for high-risk malignancies and blood disorders. Testing included cancer whole exome sequencing (WES) of matched tumor-normal samples or targeted sequencing of 467 cancer-associated genes, when sample adequacy was a concern, and tumor transcriptome (RNA-seq). A multidisciplinary molecular tumor board conducted interpretation of results and final tiered reports were transmitted to the electronic medical record according to patient preferences. Results Sixty-nine samples from 56 patients with high-risk hematologic malignancies and blood disorders were sequenced. Patients carried diagnoses of myeloid malignancy (n = 25), lymphoid malignancy (n = 25), or histiocytic disorder (n = 6). Six patients had only constitutional WES, performed for a suspicion of an inherited predisposition for their disease. For the remaining 50 patients, tumor was sequenced with matched normal tissue when available. The mean number of somatic variants per sample was low across the different disease categories (2.85 variants/sample). Interestingly, a gene fusion was identified by RNA-seq in 58% of samples who had adequate RNA available for testing. Molecular profiling of tumor tissue led to clinically impactful findings in 90% of patients. Forty patients (80%) had at least one targetable gene variant or fusion identified in their tumor tissue; however, only seven received targeted therapy. Importantly, NGS findings contributed to the refinement of diagnosis and prognosis for 34% of patients. Known or likely pathogenic germline alterations were discovered in 24% of patients involving cancer predisposition genes in 12% of cases. Conclusion Incorporating whole exome and transcriptome profiling of tumor and normal tissue into clinical practice is feasible, and the value that comprehensive testing provides extends beyond the ability to target-specific mutations.